Updating Stiffness and Hysteretic Damping Matrices Using Measured Modal Data - Jiashang Jiang; Yongxin Yuan (Shock and Vibration)
A new direct method for the finite element (FE) matrix updating problem in a hysteretic (or material) damping model based on measured incomplete vibration modal data is presented. With this method, the optimally approximated stiffness and hysteretic damping matrices can be easily constructed. The physical connectivity of the original model is preserved and the measured modal data are embedded in the updated model. The numerical results show that the proposed method works well.